2009
DOI: 10.1103/physreve.79.031706
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved x-ray studies of the dynamics of smectic-Alayer realignment by magnetic fields

Abstract: While the rotation of smectic layers under an applied field may at first appear to be a relatively simple problem, the dynamic processes involved are rather complex. An applied field produces a torque on the liquid crystal director, but has no direct influence on the smectic layers. If the director is reoriented significantly, however, the layers must also reorient in order to accommodate this (the layered structure is produced by short-range molecular interactions). Indeed, if the liquid crystalline order is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…3(a). This continuous microdomain rotation in a bulk nematic state stands in contrast with the noncontinuous nature of director reorientation observed by time resolved studies in smectic A thin films as recently reported [26] and the overall complexity of reorientation in the smectic state [27]. The intensity variations of the microdomain scattering, integrated azimuthally AE15 around ¼ 90 and ¼ 180 are shown in Fig.…”
Section: (D) the Resultsmentioning
confidence: 58%
“…3(a). This continuous microdomain rotation in a bulk nematic state stands in contrast with the noncontinuous nature of director reorientation observed by time resolved studies in smectic A thin films as recently reported [26] and the overall complexity of reorientation in the smectic state [27]. The intensity variations of the microdomain scattering, integrated azimuthally AE15 around ¼ 90 and ¼ 180 are shown in Fig.…”
Section: (D) the Resultsmentioning
confidence: 58%
“…The requirement to use superconducting magnets is a severe complication. Some static on-line X-ray experiments are published [95,96] and even some dynamic studies, where the sample was rotated inside the magnetic field and observed whilst rotating back [97,98]. For neutron experiments, occasionally an off-line magnet was used to produce aligned samples from fibrous biological macromolecules [99,100] and more recently the use of an on-line 8 T magnet to measure alignment by SANS of bicelles complexed with lanthanides was reported [101].…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%
“…The hot stage was mounted on a custom-built rotation stage described previously. [25,26] The rotation stage allows the sample to be tilted relative to the direction of propagation of the beam, in order to change the angle of incidence on the sample, and rotated about the direction of propagation of the beam, in order to orient the nematic director relative to the direction of polarisation of the fundamental beam. A pulsed, Q-switched Nd:YAG laser (Spectron Lasers, SL804 1615) was used to provide a linearly polarised, near infrared (NIR) fundamental beam of wavelength 1064 nm and diameter 1.8 mm.…”
Section: Measurement Of the Sh Signalmentioning
confidence: 99%